2011
DOI: 10.1007/s00384-011-1313-6
|View full text |Cite
|
Sign up to set email alerts
|

An international, multicentre, prospective, randomised, controlled, unblinded, parallel-group trial of robotic-assisted versus standard laparoscopic surgery for the curative treatment of rectal cancer

Abstract: In many centres, robotic-assisted surgery is being implemented on the basis of theoretical advantages, which have yet to be confirmed in practice. Robotic surgery is an expensive health care provision and merits robust evaluation. The ROLARR trial is a pragmatic trial aiming to provide a comprehensive evaluation of both robotic-assisted and standard laparoscopic surgery for the curative resection of rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
123
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 244 publications
(132 citation statements)
references
References 32 publications
4
123
0
5
Order By: Relevance
“…They will additionally compare the CRM and pathological involvement rates, the short-and longterm local recurrence rates, as well as long-term DFS and OS. The results of this study are greatly anticipated and will provide a significant amount of potentially useful and definitive information about the benefits of robotic surgery for rectal cancer as compared to laparoscopic surgery [27].…”
Section: Oncologic Outcomesmentioning
confidence: 99%
“…They will additionally compare the CRM and pathological involvement rates, the short-and longterm local recurrence rates, as well as long-term DFS and OS. The results of this study are greatly anticipated and will provide a significant amount of potentially useful and definitive information about the benefits of robotic surgery for rectal cancer as compared to laparoscopic surgery [27].…”
Section: Oncologic Outcomesmentioning
confidence: 99%
“…60 This has been criticized to be due to the lower-than-expected 12.2% conversion rate in the laparoscopic arm -the power calculation for this randomized study had been based on the results of the MRC CLASICC trial. In the only meta-analysis consisting solely of randomized controlled trials, Liao et al showed a significantly lower conversion rate in robotic TME than laparoscopy (OR 0.25, 95% CI 0.07-0.91, p=0.04).…”
Section: Use Of the XI In Tmementioning
confidence: 99%
“…There were no significant differences in operation time, length of hospital stay, time to resume regular diet, postoperative morbidity and mortality, or the oncological accuracy of resection. The ROLARR trial is an ongoing pan-world RCT that is comparing robotic versus laparoscopic resection for rectal cancer that may guide future use of robotic surgery [66].…”
Section: Management Of Early Rectal Cancer and The Malignant Polypmentioning
confidence: 99%